Pengaruh Inflasi, Nilai Tukar Rupiah, dan Suku Bunga BI terhadap Harga Saham Perusahaan Sub Sektor Properti dan Real Estate yang Terdaftar di BEI Periode 2016-2020 - Ratna Wahyuni Pratiwi; Jojok Dwiridotjahjono (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This research aims to determine the simultaneous and partial influence of inflation, Rupiah exchange rate, and Bank Indonesia interest rate against the share price of the company's Sub-sector property and Real Estate listed on Indonesia Stock Exchange period 2016-2020. The object of this research is the share price of company Sub sector property and Real Estate. This research has a population of 47 companies with sampling using purposive sampling, resulting in samples amounting to 32 companies. Research analysis techniques use multiple liner regression analysis techniques. The hypothesis test uses the F and T test. The results of simultaneous testing analysis, it is known that the variable inflation, Rupiah exchange rate, and Bank Indonesia interest rates are significantly significant to the share price of company Sub-sector and Real Estate companies. Partial inflation is significantly positive and significant, the Rupiah exchange rate has no effect, Bank Indonesia's interest rate is negatively and significantly impacted by the company's share price of Sub property and Real Estate. Keywords: Stock market, Inflation, Exchange Rate, Real Estate, Property sub sector